1990
DOI: 10.1037/0022-0663.82.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Children's reluctance to seek help with schoolwork.

Abstract: Elementary-school children were asked why they do, or do not, ask for help from parents, teachers, and classmates when they have problems in math and reading. Responses were correlated with achievement scores. Findings indicate (a) Classmates are seen as less helpful than adults in answering questions, (b) there is more concern about possible negative reactions (i.e., perceptions of being "dumb") from classmates than from adults, (c) children perceive a greater need for help in math than in reading, (d) girls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
1
22

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(198 citation statements)
references
References 38 publications
12
163
1
22
Order By: Relevance
“…[14] It also has been shown that women tend to ask more questions, thus they seek help more often than their male counterparts. [10] These findings are supported by our previous research from the fall 2012 semester, when 76% of females and 60% of males used some form of SI, and from the fall 2013 semester, when 82% of females and 60% of males used some form of SI.…”
Section: Gender Differences In Use Of Sisupporting
confidence: 79%
“…[14] It also has been shown that women tend to ask more questions, thus they seek help more often than their male counterparts. [10] These findings are supported by our previous research from the fall 2012 semester, when 76% of females and 60% of males used some form of SI, and from the fall 2013 semester, when 82% of females and 60% of males used some form of SI.…”
Section: Gender Differences In Use Of Sisupporting
confidence: 79%
“…At best, groups can try to avoid creating a more negative impression through seeking help. After all, seeking help could be viewed as a sign of incompetence and powerlessness (e.g., Nadler, 1987;Newman & Goldin, 1990). As a result, relational conflict can activate a need for more autonomy, and group members involved in relational conflict should exhibit more help avoidance than group members involved in task conflict.…”
Section: Seeking Outgroup Help In Conflict Situationsmentioning
confidence: 99%
“…For example, Newman and Goldin (1990) found that children refrained from seeking help with their schoolwork out of fear of being perceived as ''dumb'' by their peers, teachers, and parents. Most of the research on help seeking and help avoidance stems from literature on individual helping, often in an educational context (e.g., Butler & Neuman, 1995;Clegg, Bradley, & Smith, 2006;Newman & Goldin, 1990;A. M. Ryan, Gheen, & Midgley, 1998).…”
mentioning
confidence: 99%
“…The vulnerability hypothesis suggests that students with low perceived competence may decide not to ask for help because by admitting that help is needed, their inadequacy is confirmed (Newman & Goldin, 1990). The consistency hypothesis posits that students with high perceptions of their abilities might decide not to ask for help because engaging in help indicates that their competence is in danger and this presents views that are inconsistent with favorable perceptions of the self (Nadler, 1983).…”
Section: Help Seeking 12mentioning
confidence: 89%